1991
DOI: 10.3171/sup.1991.75.1s.0s59
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ICP instability and hypotension on outcome in patients with severe head trauma

Abstract: ✓ This study describes the relationship between raised intracranial pressure (ICP), hypotension, and outcome from severe head injury. The study is based on information derived from the Traumatic Coma Data Bank where ICP records from a relatively large number of patients were available to help delineate the major factors influencing outcome. From the total data base of 1030 patients, 428 met minimum monitoring duration criteria for inclusion in the present analysis. Outcome was classified according to the Glasg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
297
0
19

Year Published

1996
1996
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 689 publications
(319 citation statements)
references
References 9 publications
3
297
0
19
Order By: Relevance
“…Prominent amongst these changes are the regular monitoring and control of intracranial pressure (ICP) and cerebral perfusion pressure (CPP) [2]. While these have not been subjected to randomised controlled trials, they are based on physiological principles [3,4,5,6], and the association of poor outcomes with physiological derangements after head injury [3,4,5,6]. Despite these findings and the fact that ICP monitoring is recommended by well disseminated guidelines [7,8], recent surveys report that less than 50% of patients with severe head injury have ICP monitoring in European centres, and hence do not receive ICP/CPP directed therapy [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Prominent amongst these changes are the regular monitoring and control of intracranial pressure (ICP) and cerebral perfusion pressure (CPP) [2]. While these have not been subjected to randomised controlled trials, they are based on physiological principles [3,4,5,6], and the association of poor outcomes with physiological derangements after head injury [3,4,5,6]. Despite these findings and the fact that ICP monitoring is recommended by well disseminated guidelines [7,8], recent surveys report that less than 50% of patients with severe head injury have ICP monitoring in European centres, and hence do not receive ICP/CPP directed therapy [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic value of secondary insults due to reduced MAR increased ICR and reduced CPP has been thoroughly examined and several outcome studies have demonstrated the adverse effect of raised ICP on mortality [4][5][6][7]. Reduced CPP was also found to be strongly correlated with mortality [8].…”
Section: Introductionmentioning
confidence: 99%
“…Over 70% of intrahospital transfers are reported as being associated with unexpected events, either equipment-or patient-related [6,7], and our findings (75%) are certainly agreeable with this. Children requiring neurocritical care are at particular higher risks with transfer, as urgent head scans are performed during periods of severe physiological instability, to diagnose or rule out a severe complication such as expanding intracranial hematoma or acute hydrocephalus [8,9]. Traditionally, scans necessitate the transfer of these children with possibly impending cerebral herniation outside the PICU environment, with multiple monitoring, infusions, and ventilation, all requiring transfer to suboptimal transport modes.…”
Section: Discussionmentioning
confidence: 99%